Mass measures with coded remote access for cyber-physical systems - Stadnyk, Bohdan; Fröhlich, Thomas; Mykyychuk, Mykola; Klos, Ihor; Yatshyshyn, Svyatoslav; Kalinovska, Iryna (Lviv Politechnic Publishing House, 2017)
The aspects of design and operation of information measuring subsystem of Cyber-Physical System of coke and chemical plant are considered. This subsystem of mass parameters definition, based on industrial internet, provides coded remote access aiming at the execution of both weighing and verification metrological operations by using an embedded multivalued mass measure. To ensure the quality and reproducibility of Cyber-Physical System a remote access on the basis of TCP/IP protocol to balances was studied and developed. Installation was equipped with the standard built-in mass measure that enabled to perform in-place operations of metrological checking, verification, calibration etc. not interrupting the production cycle.
Keywords: information-measuring subsystem; cyberphysical system; coded remote access; embedded multivalued mass measure